Fatigue and Physical Activity Levels of Smoking and Non-smoking Healthy Sedentary Individuals - DEMİRBÜKEN, İLKŞAN; ZENGİN, ORHAN; YURDALAN, SAADET UFUK (AVES PRESS LTD, 2016)
Objective: This study aimed to investigate the fatigue and physical activity levels of smoking and non-smoking healthy sedentary individuals. Methods: The study was conducted with 191 sedentary university students who were informed regarding the study (age of smoking individuals, 21.01 +/- 1.34 years and age of non-smoking individuals, 20.76 +/- 1.65 years). The short form of the International Physical Activity Questionnaire was used to assess the physical activity levels, and the Piper Fatigue Scale was used to assess the fatigue levels. Results: There were no significant differences between the high, moderate, low intensity, and total physical activity levels of smoking and non-smoking healthy sedentary individuals (p>0.05). There was no statistical difference between the emotional fatigue levels of smoking and non-smoking healthy sedentary individuals (p>0.05), while statistically higher cognitive, sensory, behavioral, and total fatigue scores were observed in smoking healthy sedentary individuals than in non-smoking healthy sedentary individuals (p<0.05). Conclusion: Smoking affects cognitive, sensory, behavioral, and total fatigue levels in young sedentary individuals. It may be useful to inform university students regarding the effects of smoking on fatigue levels with respect to public health.
Keywords: Physical activity; carbon monoxide; cardiopulmonary effect; fatigue level